2019
DOI: 10.3390/molecules24010193
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Green Tea Polyphenols Against Prostate Cancer

Abstract: Prostate cancer is the most common cancer among men. Green tea consumption is reported to play an important role in the prevention of carcinogenesis in many types of malignancies, including prostate cancer; however, epidemiological studies show conflicting results regarding these anti-cancer effects. In recent years, in addition to prevention, many investigators have shown the efficacy and safety of green tea polyphenols and combination therapies with green tea extracts and anti-cancer agents in in vivo and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 134 publications
0
65
0
5
Order By: Relevance
“…Regarding more specifically PCa, in vivo pre-clinical studies have evidenced the chemopreventive effect of natural compounds in PCa xenograft mouse models and in transgenic mouse models. Although the association between polyphenols intake and tumorigenesis of PCa needs to be confirmed by large-scale epidemiological data [32], since results are sometimes inconsistent and conflicting, there is a general agreement that consumption of flavonoids in the diet significantly reduces PCa risk [33][34][35][36][37].…”
Section: Delphinidin Cyanidin Peonidinnmentioning
confidence: 99%
“…Regarding more specifically PCa, in vivo pre-clinical studies have evidenced the chemopreventive effect of natural compounds in PCa xenograft mouse models and in transgenic mouse models. Although the association between polyphenols intake and tumorigenesis of PCa needs to be confirmed by large-scale epidemiological data [32], since results are sometimes inconsistent and conflicting, there is a general agreement that consumption of flavonoids in the diet significantly reduces PCa risk [33][34][35][36][37].…”
Section: Delphinidin Cyanidin Peonidinnmentioning
confidence: 99%
“…The active pharmacological ingredient of green tea is epigallocatechin-3-gallate, EGCG [ 11 ]. EGCG is believed to contribute to various cancer-preventive effects resulting from its high antioxidant potential [ 11 14 ]. In vitro and animal studies reported a number of cancer-preventative effects of EGCG including: attenuation of oxidative stress, inhibition of angiogenesis, induction of apoptosis and alterations in expression of cell cycle regulatory proteins [ 11 , 12 , 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that the discrepancy between the topical and oral administration of EGCG is due to inadequate EGCG supply to the skin after oral ingestion. An investigation confirmed the protective activities of topical green tea phenols against UV radiation-induced erythema in a cohort of human volunteers [ 169 ]. Furthermore, it was demonstrated in a single-blind, randomized clinical trial of 50 volunteers that, compared to the placebo group, supplementation of oral green tea extract with vitamin C did not exhibit effectively decreased leukocyte infiltration or skin erythema [ 170 ].…”
Section: Dietary Phytochemicals For Skin Cancer Therapymentioning
confidence: 86%